(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The division of the Kazakh antroponimis is considered in article, taking into consideration different literature works of scientisis. There is also a need of reevaluation different materials clssifikations developed by explorers. Both why we need to consider antroponims to be the part of the language which is closely attached to the history. The article history anthroponyms scientific basis, linguistic fact to base seven periods considered separately. Given linguistic fact anthroponomy called periods consumed being selected concretized. Systematic division of historical periods chosen for the future of science anthroponyms very useful language study their support of the new theory suggest opening instruct on the right path.